APPROPRIATE DOSE OF PGPR ANTIFUNGAL TO INHIBIT FUNGI THAT CAUSE ROTTEN ON THE RHIZOME OF RED GINGER (Zingiber officinale var. Rubra) - Sriwulan Sriwulan; Hesti Kurniahu; Riska Andriani (JURNAL PENA SAINS, 2019)
Red ginger (Zingiber officinale var. Rubra) is one of the leading commodities producing essential oils and oleoresins. In red ginger cultivation, several obstacles were encountered, including the fungus attack, which caused rotten rhizome, so that the nursery process failed. Generally, fungicides are given to control the fungus. However, chemical fungicides can harm health and the environment. Therefore natural environment fungicides are needed. PGPR has antifungal activity.  It can use as a natural fungicide. This study aims to determine the antifungal activity of PGPR against fungi that cause rotten red ginger rhizomes in the nursery process using doses of 0%, 25%, 50%, 75%, and 100%. The results, the 75% PGPR dose, give the highest average inhibitory zone to fungi causing rhizome in red ginger but not significantly different from the 100% dose. Furthermore, at a dose of 75%, the resistance of fungal growth amounted to 26.7%. The use of PGPR at appropriate dosages will induce the growth of fungi that cause rot in the rhizome of Red Ginger.